Notes on Cyclanthera brachystachya (Ser.) Cog.: Morphology, Ecology, and Its New Distribution - Efendi, Muhammad; Rugayah, Rugayah (Biogenesis: Jurnal Ilmiah Biologi, 2019)
Cyclanthera brachystachya (Cucurbitaceae) is an exotic species in Indonesia that originated from America. This species was reported running wild in several places in Java for decade ago. However, it is limited information to support this statement. This needs to be done, because C. brachystachya have potentially to increase the genetic resources of cucumber family in Indonesia. The methods used include morphological and ecological observation, including their distribution from their naturalized habitat in Indonesia. Morphology of this specieswere described based on living material fromCibodas Botanical Garden area. Morphologically, it is not different with other morphology description on flora of Java and other literatures. In their natural habitat, they grow on open areas with high humidity levels and variously substrate. This species spreads in the mountain of West Java, from Mt. Gede Pangrango to Mt. Manglayang Bandung and Garut. A new distribution in Sumatera added outside range of this species in their origin area in Indonesia.